Food-Borne Trematodiases - Jennifer Keiser; Jürg Utzinger (2009)
SUMMARY An estimated 750 million people are at risk of infections with food-borne trematodes, which comprise liver flukes ( Clonorchis sinensis , Fasciola gigantica , Fasciola hepatica , Opisthorchis felineus , and Opisthorchis viverrini ), lung flukes ( Paragonimus spp.), and intestinal flukes (e.g., Echinostoma spp., Fasciolopsis buski , and the heterophyids). Food-borne trematodiases pose a significant public health and economic problem, yet these diseases are often neglected. In this review, we summarize the taxonomy, morphology, and life cycle of food-borne trematodes. Estimates of the at-risk population and number of infections, geographic distribution, history, and ecological features of the major food-borne trematodes are reviewed. We summarize clinical manifestations, patterns of infection, and current means of diagnosis, treatment, and other control options. The changing epidemiological pattern and the rapid growth of aquaculture and food distribution networks are highlighted, as these developments might be associated with an elevated risk of transmission of food-borne trematodiases. Current research needs are emphasized.